Topology optimization of mechanical structures in stair-climbing assistive technology. Issue 2 (22nd November 2019) - Verma, Abhishek; Singh, Amandeep; Ramkumar, Janakarajan
Abstract : The design of ambient assistive technology, such as a wheelchair, is less explored from the engineering design perspective compared with other products of similar platforms, such as bicycles and small vehicles. A generic engineering design of mechanical products is explored using computational tools, such as finite-element analysis and integer programming software. Topology optimization of mechanical structures is a widely explored domain that exploits the union of both finite-element analysis and linear or non-linear convergence algorithms, such as Lagrangian multiplier. Analytical modeling of material properties, such as density, using 'solid isotropic material with penalization' helps a design engineer discretize the design domain and solve for the optimization of material properties, such as stiffness, loads and energy. This paper addresses solving a wheelchair-structure-optimization problem with compliance of low energy or minimum deflection of the structure. The wheelchair is designed according to loading patterns that occur in the Indian population using male and female anthropometric data. The wheelchair structures that are optimized in this paper are designed for normal-plane and slant-plane movements. The Lagrangian multiplier convergence algorithm is taken as the constraint function for material removal after obtaining an optimal criterion for multipoint load application and multiple degrees of freedom in the structure.